2020
DOI: 10.1093/mnras/staa294
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Type Iax supernova progenitor systems with stellar population age dating

Abstract: Type Iax supernovae (SNe Iax) are the most common class of peculiar SNe. While they are thought to be thermonuclear white-dwarf (WD) SNe, SNe Iax are observationally similar to, but distinct from SNe Ia. Unlike SNe Ia, where roughly 30% occur in early-type galaxies, only one SN Iax has been discovered in an early-type galaxy, suggesting a relatively short delay time and a distinct progenitor system. Furthermore, one SN Iax progenitor system has been detected in pre-explosion images with its properties consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 103 publications
1
10
0
Order By: Relevance
“…SN 2012Z could be the first ever thermonuclear SN with a detected progenitor system, and thus linked to the singledegenerate (SD) scenario by direct observational evidence. The model of SNe Iax originating from WD-He star systems is supported by the generally young ages of SNe Iax environments (Lyman et al 2018;Takaro et al 2020), though at least one SN Iax exploded in an elliptical galaxy (Foley et al 2010a). The detection of helium is also reported in the spectra of SNe 2004cs and 2007J (Foley et al 2013;Jacobson-Galán et al 2019;Magee et al 2019), but there is a debate on the real nature of these two objects (see White et al 2015;Foley et al 2016).…”
mentioning
confidence: 89%
“…SN 2012Z could be the first ever thermonuclear SN with a detected progenitor system, and thus linked to the singledegenerate (SD) scenario by direct observational evidence. The model of SNe Iax originating from WD-He star systems is supported by the generally young ages of SNe Iax environments (Lyman et al 2018;Takaro et al 2020), though at least one SN Iax exploded in an elliptical galaxy (Foley et al 2010a). The detection of helium is also reported in the spectra of SNe 2004cs and 2007J (Foley et al 2013;Jacobson-Galán et al 2019;Magee et al 2019), but there is a debate on the real nature of these two objects (see White et al 2015;Foley et al 2016).…”
mentioning
confidence: 89%
“…For peculiar SNe Ia we apply the same SN rate model used for normal SNe Ia with some variations. 91bg-like SNe Ia primarily explode in E/S0 galaxies (Howell 2001;Li et al 2011), while SNe Iax are rarely found in early-type galaxies (Takaro et al 2020). Therefore, we set the rate of 91bg-like (SNe Iax) to be zero in star forming (passive) galaxies.…”
Section: Simulating Host Galaxies Of Sne Iamentioning
confidence: 99%
“…The colour evolution and scatter of SNe Iax are poorly understood. However, as SNe Iax are believed to explode in younger environments (Takaro et al 2020), and are therefore likely to be affected by dust, we opt to use dust extinction to introduce variation in the colour of the models. The reddening within the host galaxy for SN 2005hk is estimated to be 𝐸 (𝐵 − 𝑉) = 0.09 (Chornock et al 2006), so we correct the PLAsTiCC SN Iax models for 𝐸 (𝐵 − 𝑉) = 0.09, and apply a range of host extinctions in the simulations.…”
Section: Simulations Of Peculiar Sne Iamentioning
confidence: 99%
“…In quest of an independent estimate of the SN Ia delay time, Maoz et al (2012) used the host galaxy stellar population as a proxy to estimate the DTD assuming that SN progenitors share the same formation history with the other stars in the host galaxy. Based on such an assumption, Takaro et al (2020) utilized Hubble Space Telescope (HST) to directly observe the stars close to 9 type Iax SNe and constrained the delay time using their nearby stellar ages as proxies. Furthermore, Panther et al (2019) utilized Integral Field Unit (IFU) facilities to acquire the galaxy spectra of 17 SN 1991bglike SNe at the sites of the SN explosions, calculated the stellar populations within ∼ 1 kpc of the SNe, and concluded that SN 1991bg-like SNe originate from an older stellar population than normal SNe Ia.…”
Section: Introductionmentioning
confidence: 99%